2015
DOI: 10.1039/c5ra06550j
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical insight into the C–H and C–C scission mechanism of ethane on a tetrahedral Pt4subnanocluster

Abstract: The activation mechanism of C2H6on a Pt4cluster has been theoretically investigated in the ground state and the first excited state potential energy surfaces at the BPW91/Lanl2tz, aug-cc-pvtz//BPW91/Lanl2tz, 6-311++G(d, p) level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…4 Later, theoretically, it was reported that the neutral clusters Pt 2 , Pt 3 , and Pt 4 can activate the first C–H bond of CH 4 with small barriers, accompanied by the breakage of the second C–H bond in CH 4 as the rate-determining step. 57 More recently, we have studied the competitive activation mechanism of C–H and C–C bonds in C 2 H 6 and/or C 3 H 8 catalyzed by the Pt n ( n = 1, 2, and 4) cluster 812 and explained why the C–H insertion product is experimentally observed while the C–C insertion product is not formed in observable quantity 8,9 and why both Pt 2 and Pt 4 clusters exhibit more promising catalytic performance toward C 2 H 6 activation compared with the Pt atom. 10,12 These experimental and theoretical studies emphasize that the size of transition-metal clusters plays an important role in the catalytic reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…4 Later, theoretically, it was reported that the neutral clusters Pt 2 , Pt 3 , and Pt 4 can activate the first C–H bond of CH 4 with small barriers, accompanied by the breakage of the second C–H bond in CH 4 as the rate-determining step. 57 More recently, we have studied the competitive activation mechanism of C–H and C–C bonds in C 2 H 6 and/or C 3 H 8 catalyzed by the Pt n ( n = 1, 2, and 4) cluster 812 and explained why the C–H insertion product is experimentally observed while the C–C insertion product is not formed in observable quantity 8,9 and why both Pt 2 and Pt 4 clusters exhibit more promising catalytic performance toward C 2 H 6 activation compared with the Pt atom. 10,12 These experimental and theoretical studies emphasize that the size of transition-metal clusters plays an important role in the catalytic reactivity.…”
Section: Introductionmentioning
confidence: 99%